Synthesis, Characterization And Evaluation Of Zinc Doped MgB4O7 Based Glass Thermoluminescence Dosimeter For Radiotherapy And Industrial Applications - Bakhsh, Muhammad (2018)
The present study is aimed to develop a highly sensitive and tissue equivalent thermoluminescent dosimeter for quality assurance in modern radiotherapy techniques and industrial applications. Series of MgB4O7 glasses, of compositions X(MgO) - 100-X(B2O3) where 35 ≤ X ≤ 45 mol%, Magnesium Borate (MB), X(ZnO) - 35-X(MgO) - 65(B2O3) where 0.1 ≤ X ≤ 1 mol%, Zinc doped Magnesium Borate (MB:Zn) and X(Li2O) - 0.4(ZnO) - 35- X (MgO) - 65(B2O3) where 0.01 ≤ X ≤ 0.1 mol%, Lithium co-doped Zinc doped Magnesium Borate (MB:Zn, Li) are synthesized using conventional melt-quenching method. The amorphous nature of synthesized samples is analysed through X-ray diffraction (XRD) and further confirmed with Field Emission Scanning Electron Microscopy (FESEM).